The Importance of Probiotics in Human and Animal Life: A Review (Razi Medical Journal, 2025)
Probiotics are live bacteria that, when given in sufficient quantities, help the host's health. They have attracted much interest lately. These good bacteria, which typically include Lactobacillus, Bifidobacteria, and Saccharomyces, improve the health of both animals and humans. Antibiotics alter the body's natural microbiota and result in vitamin deficiencies because they cannot distinguish between healthy and bad bacteria. They also significantly reduce the host's defenses by killing beneficial bacteria in the vaginal and intestinal tracts. Because of their positive impacts on human health, including metabolism and immune function, probiotics—a colony of bacteria that reside in our intestines—are thought of as a metabolic "organ." In therapeutic contexts, they treat and prevent diseases like autism, migraine, Helicobacter pylori infection, colon cancer, hypertension, diabetes, acute pancreatitis, diarrhea, and ventilator-associated pneumonia. By enhancing gut barrier function, modifying microbial habitat in the intestine, boosting innate and adaptive immune responses, promoting competitive adhesion to the mucosa and epithelium, and generating antimicrobial chemicals, probiotics may change immunological activity. The purpose of this study is to list the important role that probiotics play in the prevention and therapeutic use of many diseases for which there may or may not be treatment options. A thorough search was conducted using keywords like probiotics, microbiota, prophylactics, and therapeutic uses in research databases like PubMed, PubMed Central (PMC), Scopus, Web of Science, Research Gate, Google Scholar, and the Cochrane Library. The main points of this succinct narrative review essay were the selection, history, mechanism/mode of action, most recent developments in therapeutic and preventative uses, and prospective avenues for probiotic use in medicinal and preventative purposes.
Keywords: Probiotics, Lactobacillus, Bifidobacteria, Saccharomyces, Good Bacteria